Diatom Biodiversity and Speciation Revealed by Comparative Analysis of Mitochondrial Genomes - Wang, Yichao; Liu, Shuya; Wang, Jing; Yao, Yanxin; Chen, Yang; Xu, Qing; Zhao, Zengxia; Chen, Nansheng (Frontiers in Plant Science, 2022)
Diatoms (Bacillariophyta) constitute one of the most diverse and ecologically significant groups of phytoplankton, comprising 100,000–200,000 species in three classes Bacillariophyceae, Mediophyceae, and Coscinodiscophyceae. However, due to the limited resolution of common molecular markers including 18S rDNA, 28S rDNA, ITS, rbcL, and cox1, diatom biodiversity has not been adequately ascertained. Organelle genomes including mitochondrial genomes (mtDNAs) have been proposed to be “super barcodes” for distinguishing diatom species because of their rich genomic content, and the rapid progress of DNA sequencing technologies that has made it possible to construct mtDNAs with increasing throughout and decreasing cost. Here, we constructed complete mtDNAs of 15 diatom species including five Coscinodiscophyceae species (Guinardia delicatula, Guinardia striata, Stephanopyxis turris, Paralia sulcata, and Actinocyclus sp.), four Mediophyceae species (Hemiaulus sinensis, Odontella aurita var. minima, Lithodesmioides sp., and Helicotheca tamesis), and six Bacillariophyceae species (Nitzschia ovalis, Nitzschia sp., Nitzschia traheaformis, Cylindrotheca closterium, Haslea tsukamotoi, and Pleurosigma sp.) to test the practicality of using mtDNAs as super barcodes. We found that mtDNAs have much higher resolution compared to common molecular markers as expected. Comparative analysis of mtDNAs also suggested that mtDNAs are valuable in evolutionary studies by revealing extensive genome rearrangement events with gene duplications, gene losses, and gains and losses of introns. Synteny analyses of mtDNAs uncovered high conservation among species within an order, but extensive rearrangements including translocations and/or inversions between species of different orders within a class. Duplication of cox1 was discovered for the first time in diatoms in Nitzschia traheaformis and Haslea tsukamotoi. Molecular dating analysis revealed that the three diatom classes split 100 Mya and many diatom species appeared since 50 Mya. In conclusion, more diatom mtDNAs representing different orders will play great dividends to explore biodiversity and speciation of diatoms in different ecological regions.